1979
DOI: 10.1111/j.1651-2227.1979.tb04989.x
|View full text |Cite
|
Sign up to set email alerts
|

Free and Bound Tryptophan in Human Plasma During the Perinatal Period

Abstract: The concentration of tryptophan and the degree of binding of the amino acid to protein were examined in human plasma during the perinatal period. Both total and unbound (free) tryptophan were higher in cord vein plasma than in the maternal circulation, the concentration gradient being approximately 1 : 2. The proportion of the total plasma tryptophan concentration that was not bound to protein was less in cord vein plasma than in the maternal circulation. After birth the proportion in infant plasma fell signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…This fact seems of particular interest especially in consideration of the fre quent utilization of elective cesarean section [25]. Furthermore, the homogeneity ob served in our results suggests that more atten tion should be paid to investigating the sup ply and utilization of tryptophan by the mother and neonate, taking into account the difference in stress, food composition, drugs administered and day-night rhythms of indi vidual mothers and neonates after particular perinatal medical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact seems of particular interest especially in consideration of the fre quent utilization of elective cesarean section [25]. Furthermore, the homogeneity ob served in our results suggests that more atten tion should be paid to investigating the sup ply and utilization of tryptophan by the mother and neonate, taking into account the difference in stress, food composition, drugs administered and day-night rhythms of indi vidual mothers and neonates after particular perinatal medical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tricklebank et al [25] and De Antoni et al [5] have found that in vaginal births the levels of both total and free trypto phan are higher in the umbilical cord than in the mother's blood at a rate of 2:1, while the percentage of free tryptophan is slightly lower in the umbilical than in the maternal plasma [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As trypto phan is an essential amino acid and crosses the hematoencephalic barrier only in the free form, the high percentage of the free form seems to guarantee a quota available for up take by the central nervous system after sud-den removal of the placenta supply line at birth [9,10]. This full homeostatic motherfetus adjustment is of particular interest, considering that the developing central ner vous system is sensitive to biochemical stress, and the role of this amino acid is important in the control of serotonin synthe sis in the brain [3,7], If we consider the needs of newborn in fants, it is known that human milk may satisfy a number of important criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on maternal, fetal and neonatal plasma have often tended to exclude trypto phan for methodological reasons, and no re ports have previously examined free trypto phan in maternal milk [6,9,10]. Conse quently little is known of the feeding factors that may influence its availability after the postnatal plasma decline of both total and free forms, following the sudden removal of the placental supply route [3,8], This information would be of clinical sig nificance, considering that tryptophan is the only amino acid that is bound to circulating plasma albumin between 80 and 90% and that the availability of the small free fraction appears to be an important factor in the con trol of the synthesis of the neurotransmitter serotonin in the brain [4,5,7], We evaluated total (protein-bound and free) and free tryptophan levels of breast milk obtained by a standard technique in a group of mothers during the first weeks of lactation.…”
Section: Introductionmentioning
confidence: 99%